2010
DOI: 10.1111/j.1467-9604.2010.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Stories from school: dyslexia and learners' voices on factors impacting on achievement

Abstract: Students with dyslexia often experience low self‐esteem and, linked with this, low academic achievement. Our research, commissioned by the Higher Education Academy, was carried out by academics in two universities, one in the south‐west of England and one in the north‐west, over 2009–2010. It set out to address ‘transitions and questions of “access” to higher education for students with identified disabilities’. While we accessed interesting material in this area we were also impressed by the wealth of materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 30 publications
6
53
0
3
Order By: Relevance
“…Specifically, a research study carried out in Australia, aimed at investigating the educational experiences of nine students with physical disabilities, found that 'although there were positive stories of friendships developing between participants and their peers without disabilities, there were also stories of loneliness and exclusion, of being a curiosity, and of not being made to feel welcome' (Curtin and Clarke 2005, 209). Similar findings were made in the studies by Cefai and Cooper (2010) and Gibson and Kendall (2010), both of which analysed disabled students' various and multi-layered social experiences at schools.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, a research study carried out in Australia, aimed at investigating the educational experiences of nine students with physical disabilities, found that 'although there were positive stories of friendships developing between participants and their peers without disabilities, there were also stories of loneliness and exclusion, of being a curiosity, and of not being made to feel welcome' (Curtin and Clarke 2005, 209). Similar findings were made in the studies by Cefai and Cooper (2010) and Gibson and Kendall (2010), both of which analysed disabled students' various and multi-layered social experiences at schools.…”
Section: Discussionsupporting
confidence: 83%
“…The vast majority of these articles generally addressed the experiences of college students with physical disabilities (n = 13;Bessant, 2012;Cortes, Hollis, Amick, & Katz, 2002;Nelson, et al, 1993;Papasotiriou & Windle, 2012;Poussu-Olli, 1999;Roessler & Kirk, 1998), with seven articles specifically discussing access issues (Gibson & Kendall, 2010;Gilson & Dymond, 2012;Israelite, Swartz, Huynh, & Tocco, 2005;Moswela & Mukhopadhyay, 2011;Opini, 2012;Parker, 1999;Wessel, Wentz, & Markle, 2011). Additionally, one article addressed self-determination (Parker, 1999), while three discussed the transition from college to career (Israelite, Swartz, Huynh, & Tocco, 2005;Roessler et al, 2009, Roessler & Kirk, 1998.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…… (2007, 287) This work suggests that practitioners and education communities should be encouraged to develop critical understandings of education in relation to its socio-cultural processes and that the field of special education and related research be considered significant in influencing the development of socio-cultural theory and its applications. Additional recommendations from this commissioned research are cited in the published paper of Gibson and Kendall (2010b) and also accessible at the Higher Education Academy -ESCalate. (2011).…”
Section: Resultsmentioning
confidence: 96%